Experimental (electrochemistry) and theoretical (ab initio and density functional theory) studies of hydrogen and sulfide adsorption on palladium (100) surface. - Angelo, ACD; Souza, A. R. de; Morgon, N. H.; Sambrano, JR (Soc Brasileira Quimica, 2001)
The adsorption of H And S2- species on Pd (100) has been studied with ab initio, density-functional calculations and electrochemical methods. A cluster of five Pd atoms with a frozen geometry described the surface. The computational calculations were performed through the GAUSSIAN94 program, and the basis functions adapted to a pseudo-potential obtained by using the Generator Coordinate Method adapted to the this program. Using the cyclic voltammetry technique through a Model 283 Potentiostat/Galvanostat E.G.&G-PAR obtained the electrochemical results. The calculated chemisorption geometry has a Pd-H distance of 1.55 Angstrom, and the potential energy surface was calculated using the Becke3P86//(GCM/DFT/SBK) methodology. The adsorption of S2- ions on Pd surface obtained both through comparison between the experimental and theoretical results, at MP2 level, suggest a S2- absorption into the metallic cluster. The produced Pd-(S2-) system was show to be very stable under the employed experimental conditions. The paper has shows the powerful aid of computational methods to interpret adsorption experimental data.
Keywords: ab initio; DFT; cyclic voltammetry; adsorption; hydrogen; sulfide